CT‐guided transthoracic needle biopsy for evaluation of PD‐L1 expression: Comparison of 22C3 and SP263 assays. Issue 7 (24th June 2019) - Beck, Kyongmin S.; Kim, Seung Joon; Kang, Jin Hyoung; Han, Dae Hee; Jung, Jung Im; Lee, Kyo Young
Abstract : Background: Although there have been several studies on concordance of different assays testing programmed cell death ligand‐1 (PD‐L1) expression using surgical specimens, studies using real‐world biopsy specimens are scarce. However, many of the non‐small cell lung cancer (NSCLC) cases requiring immunotherapy and thus PD‐L1 testing are unresectable having to rely on small biopsy results. Therefore, we sought to assess the concordance of two diagnostic assays (22C3 and SP263) in evaluating PD‐L1 expression using specimens from CT‐guided transthoracic needle biopsy (TNB) specimens in a routine clinical setting. Methods: A total of 202 NSCLC cases that underwent CT‐guided TNB from April 2017 to February 2018 were retrospectively reviewed. Biopsy specimens tested with both 22C3 and SP263 assays were included. Concordance of PD‐L1 expression levels determined by two assays was assessed using intraclass correlation coefficient, and the agreement of dichotomized values at various cutoffs (1%, 25%, and 50%) were assessed using Cohen's κ coefficient of agreement. Results: A total of 80 patients (M:F = 47:33, mean age: 68.0 years) were included in the study. Concordance of PD‐L1 expression levels was high (intraclass coefficient: 0.892) between 22C3 and SP263 assays. Agreements at cutoff levels of 1%, 25%, and 50% were also good, with κ values of 0.878, 0.698, and 0.790, respectively. Positive percent agreement was 93.2%, 100.0%, and 95.2% for agreements at 1%, 25%, and 50%. Conclusion: There is a high concordance of PD‐L1 expression evaluated with 22C3 and SP263 assays using CT‐guided TNB specimens.